The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.gendis.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic role of LncZBTB39-1:2 in the trophoblast mobility of preeclampsia

Abstract: Preeclampsia is characterized by new onset of hypertension and proteinuria after 20 weeks' gestation and is a leading cause of maternal and neonatal morbidity and mortality. The pathogenesis of preeclampsia is often associated with aberrant trophoblast function that leads to shallow placental implantation. However, the exact underlying mechanisms remain unclear. Placental LncZBTB39-1:2 expression level was investigated in 20 healthy placentae and 20 placentae with preeclampsia using qRT-PCR, and the metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…At present, increasing numbers of investigations have suggested that the occurrence of PE is associated with the abnormal energy metabolism. The expression of lncZBTB39-1:2 in placenta has the potential of decreasing the trophoblast activity by means of impacting the energy regulation, which may promote the progress of PE [73].…”
Section: Lncrnas Affect Decidualization and Energy Metabolism In Pementioning
confidence: 99%
“…At present, increasing numbers of investigations have suggested that the occurrence of PE is associated with the abnormal energy metabolism. The expression of lncZBTB39-1:2 in placenta has the potential of decreasing the trophoblast activity by means of impacting the energy regulation, which may promote the progress of PE [73].…”
Section: Lncrnas Affect Decidualization and Energy Metabolism In Pementioning
confidence: 99%
“…Evidence suggests that preeclamptic placentas presented with mitochondrial dysfunction [ 44 ] and glycolytic inhibition [ 45 ]. It has been reported that cell migration demands a large amount of energy generated from mitochondria [ 46 ], and that dysfunction in aerobic respiration attenuated trophoblast migration [ 47 ]. Liang et al demonstrated that inhibition of aerobic glycolysis impaired EMT, migration and invasion of trophoblast [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal placentation (invasion of spiral arteries by trophoblast) leads to maternal inflammatory response secondary to oxidative stress. 12,32 On molecular level, some authors stress the role of the inflammatory cytokines, endothelial dysfunction, imbalance between proangiogenic and antiangiogenic factors, 33 defective replacement of epithelial cadherin by vascular endothelial cadherin, decreased preimplantation factor (PIF) normally promoting trophoblast invasion, reducing oxidative stress and downregulating annexin A2 gene and protein levels in the endometrium, elevated circulating sFlt1 levels, or impaired ELABELA action normally stimulating the invasion and migration of trophoblastic cells through the activation of downstream Pl3K/AKT/mTOR pathway. [34][35][36][37] The placentas from high-risk pregnancies are notorious for the coexistence of various lesions and patterns of injury, socalled overlap lesions and patterns, 16 hypoxic, thrombotic, inflammatory, fetal vascular malperfusion, maternal vascular malperfusion, etc.…”
Section: Discussionmentioning
confidence: 99%
“…On molecular level, some authors stress the role of the inflammatory cytokines, endothelial dysfunction, imbalance between proangiogenic and antiangiogenic factors, 33 defective replacement of epithelial cadherin by vascular endothelial cadherin, decreased preimplantation factor (PIF) normally promoting trophoblast invasion, reducing oxidative stress and downregulating annexin A2 gene and protein levels in the endometrium, elevated circulating sFlt1 levels, or impaired ELABELA action normally stimulating the invasion and migration of trophoblastic cells through the activation of downstream Pl3K/AKT/mTOR pathway. 34 35 36 37…”
Section: Discussionmentioning
confidence: 99%